A veritable menagerie of heritable bacteria from ants, butterflies, and beyond: broad molecular surveys and a systematic review. - Jacob A Russell; Colin F Funaro; Ysabel M Giraldo; Benjamin Goldman-Huertas; David Suh; Daniel J C Kronauer; Corrie S Moreau; Naomi E Pierce (PLoS ONE)
Maternally transmitted bacteria have been important players in the evolution of insects and other arthropods, affecting their nutrition, defense, development, and reproduction. Wolbachia are the best studied among these and typically the most prevalent. While several other bacteria have independently evolved a heritable lifestyle, less is known about their host ranges. Moreover, most groups of insects have not had their heritable microflora systematically surveyed across a broad range of their taxonomic diversity. To help remedy these shortcomings we used diagnostic PCR to screen for five groups of heritable symbionts-Arsenophonus spp., Cardinium hertigii, Hamiltonella defensa, Spiroplasma spp., and Wolbachia spp.-across the ants and lepidopterans (focusing, in the latter case, on two butterfly families-the Lycaenidae and Nymphalidae). We did not detect Cardinium or Hamiltonella in any host. Wolbachia were the most widespread, while Spiroplasma (ants and lepidopterans) and Arsenophonus (ants only) were present at low levels. Co-infections with different Wolbachia strains appeared especially common in ants and less so in lepidopterans. While no additional facultative heritable symbionts were found among ants using universal bacterial primers, microbes related to heritable enteric bacteria were detected in several hosts. In summary, our findings show that Wolbachia are the dominant heritable symbionts of ants and at least some lepidopterans. However, a systematic review of symbiont frequencies across host taxa revealed that this is not always the case across other arthropods. Furthermore, comparisons of symbiont frequencies revealed that the prevalence of Wolbachia and other heritable symbionts varies substantially across lower-level arthropod taxa. We discuss the correlates, potential causes, and implications of these patterns, providing hypotheses on host attributes that may shape the distributions of these influential bacteria.